A Furniture Sales Profit Using the Tsukamoto Method: Indonesia, - Dzakwan Adib; ADAM, ADAM TAUFFIQURRAHMAN; Tri Hastono; Diky Setiawa (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2024)
Abstract. Optimal profit can be achieved through maximum sales results with minimal costs. Besides meeting market demand, cost utilization is also a crucial factor in determining optimal outcomes (Muflikhudin 2021). To address the challenges faced by the discount store in Sampit, several necessary steps should be taken. These include analyzing customer demand data by having the store owner pay attention to frequently requested items. Additionally, enhancing product availability by increasing inventory levels and implementing more effective inventory management systems through various methods to prepare product stocks (Beu and Husna 2019). The aim of this research is to predict revenue for a specific period based on sales turnover (Rahmawati, Rahima Dina, and Wartono 2020).